Creativity in writing poetry texts using web-based canva - Caca Hidayat; Dida Firmansyah; Teti Sobari (JLER (Journal of Language Education Research), 2026)
Classroom Action Research (CAR) aims to describe the results of improving the ability to write poetry about students of class X Semester II SMA Negeri 1 Saguling New Year's Eve 2023/2024 modified poetry writing using web canva as a source of ideas. Observation data Disruptors Students are analyzed qualitatively using the Observation Sheet for the activity of Disruptors and teachers. The results of poetry writing, quantitative analysis using descriptive analysis. Based on the results of data analysis with a discussion of the results of the researcher, it can be continued that writing poetry using web canvas text can improve the ability to write poetry Disruptors of class X Semester II SMA Negeri 1 Saguling. Distance learning with an increase in results from 77.14% Cycle I to 94.29% Cycle II. Disruptors' poetry writing abilities can be seen, both in the teaching and learning process and through the results of Disruptors' Poetry Writing Works about pesto. At the evaluation stage, the results of the Disruptors' test that have been evaluated Menu There is an increase in the learning process Writing using web canva.